Insight into antioxidant-like activity and computational exploration of identified bioactive compounds in Talinum triangulare (Jacq.) aqueous extract as potential cholinesterase inhibitors - Olakunle Bamikole Afolabi; Oluwaseun Ruth Olasehinde; Olutunmise Victoria Owolabi; Kikelomo Folake Jaiyesimi; Funmilayo Deborah Adewumi; Olajumoke Tolulope Idowu; Samson Olatunde Mabayoje; Adejoke Olukayode Obajuluwa; Oghenerobor Benjamin Akpor (BMC, 2024)
Abstract Background Recent reports have highlighted the significance of plant bioactive components in drug development targeting neurodegenerative disorders such as Alzheimer's disease (AD). Thus, the current study assessed antioxidant activity and enzyme inhibitory activity of the aqueous extract of Talinum triangulare leave (AETt) as well as molecular docking/simulation of the identified phytonutrients against human cholinesterase activities. Methods In vitro assays were carried out to assess the 2,2- azinobis (3-ethyl-benzothiazoline-6-sulfonic acid) (ABTS) cation radicals and cholinesterase inhibitory activities of AETt using standard protocols. High performance liquid chromatography coupled with diode-array detection (HPLC-DAD) was employed to identify compounds in AETt. Also, for computational analysis, identified bioactive compounds from AETt were docked using Schrodinger's GLIDE against human cholinesterase obtained from the protein data bank ( https://www.rcsb.org/ ). Results The results revealed that AETt exhibited a significant concentration-dependent inhibition against ABTS cation radicals (IC50 = 308.26 ± 4.36 µg/ml) with butylated hydroxytoluene (BHT) as the reference. Similarly, AETt demonstrated a significant inhibition against acetylcholinesterase (AChE, IC50 = 326.49 ± 2.01 µg/ml) and butyrylcholinesterase (BChE, IC50 = 219.86 ± 4.13 µg/ml) activities with galanthamine as the control. Molecular docking and simulation analyses revealed rutin and quercetin as potential hits from AETt, having showed strong binding energies for both the AChE and BChE. In addition, these findings were substantiated by analyses, including radius of gyration, root mean square fluctuation, root mean square deviation, as well as mode similarity and principal component analyses. Conclusion Overall, this study offers valuable insights into the interactions and dynamics of protein-ligand complexes, offering a basis for further drug development targeting these proteins in AD.